Electro-mechanical performance of smart piezoelectric nanocomposite plates reinforced by zinc oxide and gallium nitride nanowires - Moradi-Dastjerdi, Rasool; Rashahmadi, Samrand; Meguid, Shaker A. (Mechanics based design of structures and machines, 2022)
The use of piezoelectric nano-fillers in a non-piezoelectric matrix is a very attractive proposition for developing smart nanocomposite materials with desired electro-mechanical properties. The eco-friendly nanowires (NWs) of zinc oxide (ZnO) and gallium nitride (GaN) are the two candidates used to introduce smart piezoelectric nanocomposite materials. Specifically, in this first effort, we examined the electro-mechanical performance of newly developed composite plates reinforced by piezoelectric ZnO NW and GaN NW of varied volume fractions. The static deflections and natural frequencies of the newly developed bimorph piezoelectric nanocomposite plates subject to electro-mechanical loads are analyzed using a mesh-free method in conjunction with the shape functions of MLS. Using third order shear deformation theory (TDST), the coupled electro-mechanical governing equations for the considered smart plates are obtained and numerically integrated. The effects of the electro-mechanical loading and plate thickness on static deflection and natural frequencies of piezoelectric plates are investigated and discussed. Our predictions reveal that the application of electrical input to the plates can induce greater deflection than the ones introduced by mechanical loads and that ZnO NWs offer greater deflection than GaN NW. However, dynamic analysis indicates that GaN NW-reinforced plates have higher natural frequencies than those reinforced by ZnO NW.